A Lumped Parameter Model for the Analysis of Dynamic Effects in Wells Turbines. (August 2018) - Virdis, Irene; Ghisu, Tiziano; Cambuli, Francesco; Puddu, Pierpaolo
Abstract: Breakwater integrated OWC/turbine systems are among the most well-known devices for wave energy conversion, thanks to the low environmental impact and costs of realization. These systems have been largely studied both experimentally and numerically, focusing either on OWC hydrodynamic or power unit performance. The turbine has been studied in experimental facilities that usually reproduced the periodic motion of the water column in the chamber by an artificially moved piston. Detailed studies highlighted a difference between turbine performance during piston acceleration and deceleration, usually attributed to a hysteretic behavior of the turbine. On the contrary, OWC performance has been generally studied either neglecting or crudely simplifying the turbine interaction. Numerical analyses on OWC systems, due their large scale, are often conducted using lumped parameter models, simplifying the effect of the turbine and therefore the bidirectional link between water column and turbine. The objective of this work is to introduce a lumped parameter model, able to reproduce the interaction of the turbine with the mass of air in the OWC chamber. The results of the proposed model are compared with experimental data and CFD analyses, and demonstrate that the hysteresis is caused by compressibility effects in the air chamber and not, as previously assumed, by a hysteresis in the turbine aerodynamics. The lumped parameter model allows to rapidly isolate the parameters with the largest influence on system performance, and could be integrated with existing zero-dimensional OWC models to improve to understanding of the hydrodynamic/aerodynamic interaction in the overall system.